Decoding the exosomal secretome: stem cell-elicted microenvironmental reprogramming for anterior cruciate ligament regenerative medicine - Chen, Junjie; He, Jiayang; Yang, Dujiang; He, Yuhan; Wei, Yuhao; Zhang, Zhiqiang; Zhou, Xue; Cheng, Ming (Frontiers in Bioengineering and Biotechnology, 2025)
The ACL rupture is a prevalent and debilitating joint injury that has garnered significant clinical and scientific interest. Surgical reconstruction is often necessary for ACL rupture, yet numerous clinical cases indicate that the outcomes of such procedures are frequently suboptimal. Research has highlighted that the treatment of ACL rupture is particularly challenging due to factors such as the inflammatory response, the formation of vascular scar tissue, and the slow healing of tendon-bone interface attachment points. These complications result in poor integration of tendon grafts within bone tunnels. Recent advancements in stem cell research have introduced new possibilities for ACL rupture treatment. However, stem cell therapy is not without its limitations, including safety concerns such as the risk of aberrant differentiation leading to oncogenesis. Exosomes, a type of extracellular vesicle secreted by stem cells, have been found to modulate immune responses, promote neovascularization, influence scar formation, and regulate bone homeostasis in vivo. This review seeks to systematically evaluate the therapeutic potential of stem cell-derived exosomes in the context of ACL rupture repair.